Jewish education from Antiquity to the Middle Ages : studies in honour of Philip S. Alexander - Brooke, George J.; Smithuis, Renate. (Ancient Judaism and Early Christianity, 2017)
In Jewish Education from Antiquity to the Middle Ages fifteen scholars offer specialist studies on Jewish education from the areas of their expertise. This tightly themed volume in honour of Philip S. Alexander has some essays that look at individual manuscripts, some that consider larger literary corpora, and some that are more thematically organised. Jewish education has been addressed largely as a matter of the study house, the bet midrash. Here a richer range of texts and themes discloses a wide variety of activity in several spheres of Jewish life. In addition, some notable non-Jewish sources provide a wider context for the discourse than is often the case.